Preparation method and application of tin-based sulfide material with nanostructure

By using chemical vapor deposition technology with FTO conductive glass and solid sulfur powder, a safe, low-cost and controllable synthesis of tin-based sulfide nanomaterials was achieved, solving the problems of complex processes and difficult phase control in existing technologies, and obtaining high-quality nanomaterials for optoelectronic and energy storage devices.

CN120987575AActive Publication Date: 2025-11-21XIANGTAN UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202511537603.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-27
Publication Date
2025-11-21
Estimated Expiration
2045-10-27

AI Technical Summary

Technical Problem

Existing methods for preparing tin-based sulfides suffer from problems such as complex processes, high costs, and difficulty in phase control, making it difficult to achieve the synthesis of high-quality, controllable tin-based sulfide nanomaterials.

Method used

Using FTO conductive glass as the tin source and growth substrate, combined with solid sulfur powder as the sulfur source, and through chemical vapor deposition technology, the amount of sulfur powder and growth temperature are controlled to achieve safe, low-cost and controllable synthesis of tin-based sulfide nanomaterials SnS2, Sn2S3, and SnS.

Benefits of technology

This study achieved efficient and controllable growth of tin-based sulfide nanomaterials, simplified the process, reduced production costs, and improved the stability and purity of the materials, making them suitable for optoelectronic devices and energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120987575A_ABST
    Figure CN120987575A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a tin-based sulfide material with a nano structure, and belongs to the technical field of nano material preparation. According to the method, based on a normal-pressure chemical vapor deposition system, FTO conductive glass serves as a tin source and a growth substrate at the same time, solid sulfur powder serves as a sulfur source, and controllable growth of different phase nanostructures such as SnS2, Sn2S3 and SnS is achieved by cooperatively regulating and controlling the dosage of the sulfur powder and the growth temperature. According to the method, the tin source is supplied in situ through FTO, the problems that in a traditional method, the tin source is unevenly conveyed, and a toxic precursor is used are effectively solved, the method has the advantages of being simple in process, safe, environmentally friendly, low in cost, high in product purity, high in phase controllability and the like, and a material basis is provided for application of tin-based sulfide in the fields of photoelectrons, energy catalysis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of group IV-VI compound nanomaterials technology, specifically relating to a method for preparing a nanostructured tin-based sulfide material and its application. Background Technology

[0002] In recent years, two-dimensional layered materials such as graphene, transition metal chalcogenides, and group IV-VI compounds have shown broad application prospects in nanoelectronics, optoelectronics, and energy catalysis due to their unique physical and chemical properties. Among them, tin-based sulfides (SnS2, Sn2S3, SnS) have shown significant potential in photovoltaic devices, energy storage systems, photocatalysis, and photoelectric detection due to their tunable band gap, high light absorption coefficient, and typical layered structure. Specifically, SnS, as an orthorhombic p-type semiconductor (band gap of approximately 1.2 eV), possesses excellent electrical and thermoelectric properties and is often used in batteries and thermoelectric materials; SnS2 is an n-type semiconductor with a hexagonal CdI2 structure (indirect band gap of approximately 2.2 eV), exhibiting significant optical anisotropy and strong ultraviolet-visible light absorption, making it suitable for photocatalysis and ultraviolet-visible light detectors. Sn2S3 is a type of tin containing mixed valence states (Sn... 2+ / Sn 4+ SnS2, an n-type semiconductor with a band gap of approximately 1.0–1.5 eV, exhibits excellent light absorption and charge transport properties, making it particularly prominent in solar cells and lithium / sodium-ion batteries. Therefore, achieving high-quality, controllable synthesis of various phases such as SnS2, Sn2S3, and SnS is a crucial prerequisite for advancing in-depth research and practical applications of this type of material.

[0003] Currently, common methods for preparing tin-based sulfides (SnS2, Sn2S3, SnS) include chemical vapor deposition (CVD), solvothermal methods, and chemical bath deposition. However, these methods still face a series of technical bottlenecks. Solvothermal methods easily introduce organic residues, resulting in cumbersome subsequent washing processes, and the drying stage may induce material oxidation. Thin films obtained through chemical bath deposition generally suffer from high impurity levels and poor adhesion, typically requiring subsequent treatment to improve crystallinity. Traditional CVD methods often rely on highly toxic or corrosive precursors (such as H2S, CS2, SnCl4), which not only imposes stringent requirements on equipment sealing and exhaust gas treatment but also significantly increases process complexity and operating costs. Furthermore, existing methods still face challenges in achieving precise control over the different phases of tin-based sulfides (SnS2, Sn2S3, SnS), making it difficult to obtain the target pure phase material within the same technical system through simple and environmentally friendly process parameter adjustments. This severely restricts the study of their intrinsic properties and their application in devices.

[0004] Therefore, developing a synthesis method that does not require high-risk precursors, has a simple process flow, and enables the controlled growth of tin-based sulfides is crucial for the practical application of this material system, and thus has great significance. Summary of the Invention

[0005] To address the technical challenges of complex processes, high costs, and difficulties in phase control in existing tin-based sulfide preparation technologies, this invention proposes a method for preparing nanostructured tin-based sulfide materials and their applications. The tin-based sulfides include at least one of SnS2, Sn2S3, and SnS. This method, based on chemical vapor deposition (CVD), employs a novel strategy of in-situ tin source supply to an FTO substrate, achieving safe, low-cost, and controllable synthesis of SnS2, Sn2S3, and SnS nanomaterials. The method is not only simple to operate, low in cost, and highly controllable, but also yields materials with excellent stability under ambient temperature conditions, laying a solid foundation for in-depth research on their physical properties.

[0006] The technical solution adopted by the present invention to achieve the above objectives is as follows:

[0007] A method for preparing a nanostructured tin-based sulfide material, wherein the tin-based sulfide includes one of SnS2, Sn2S3, and SnS, the preparation method is based on a chemical vapor deposition system, using FTO conductive glass as the tin source and growth substrate, and solid sulfur powder as the sulfur source, and includes the following steps:

[0008] S1. Place the FTO conductive glass in the constant temperature heating zone of the chemical vapor deposition system;

[0009] S2. Place the source boat containing sulfur powder upstream of the constant temperature heating zone;

[0010] S3. Introduce a mixture of protective gas and reducing gas into the chemical vapor deposition system;

[0011] S4. The constant temperature heating zone is heated to 500℃~600℃ and kept at that temperature to allow the tin element released from the FTO conductive glass to react with gaseous sulfur, thereby growing a nanostructured tin-based sulfide material in situ on the substrate.

[0012] In this method, by adjusting the amount of sulfur powder and the growth temperature of the constant-temperature heating center region, selective control of the tin-based sulfide phase can be achieved, thereby obtaining one of the target tin-based sulfides SnS2, Sn2S3, and SnS.

[0013] Furthermore, the specific methods for achieving selective control are as follows:

[0014] When the amount of sulfur powder used is 100~250 mg and the growth temperature is 500~550℃, the target tin-based sulfide is SnS2.

[0015] When the amount of sulfur powder used is 25~75 mg and the growth temperature is 500~550℃, the target tin-based sulfide is Sn2S3.

[0016] When the amount of sulfur powder used is 80~120 mg and the growth temperature is 580~600℃, the target tin-based sulfide is SnS.

[0017] Furthermore, in step S1, the sheet resistance of the FTO conductive glass is 7 to 14 ohms, and the thickness is 1.8 to 3.5 mm, preferably 2.0 to 2.5 mm; FTO is used as both the substrate and the tin source. This design enables full utilization of tin and avoids the problems of low tin source transport efficiency and uneven supply that exist with powdered tin sources.

[0018] Furthermore, in step S1, the growth substrate is FTO. The surface and interface characteristics of the substrate are one of the decisive factors for the growth of tin-based sulfide SnS2, Sn2S3, and SnS nanostructures. The F ions doped in the SnO2 layer on the FTO surface can effectively promote the growth of tin-based sulfide SnS2, Sn2S3, and SnS nanosheet materials.

[0019] Furthermore, in step S2, the purity of the sulfur powder is not less than 99.9%, and the distance between the source boat and the center of the isothermal heating zone is 21.5 cm to 24.5 cm. The source boat is a high-temperature resistant container such as a quartz boat or a ceramic boat. In chemical vapor deposition, the loading amount of high-purity sulfur source directly affects the saturated vapor pressure of sulfur in the air, thereby regulating the growth kinetics of SnS2, Sn2S3, and SnS nanomaterials. By optimizing the distance between the source boat and the center of the isothermal heating zone, the precursor vapor can be directionally transported under the drive of the mixed carrier gas, effectively preventing runaway nucleation caused by premature thermal decomposition. Experimental data confirm that an axial spacing of 21.5–24.5 cm can precisely control the partial pressure of sulfur vapor within the optimal process range, achieving a synergistic balance between surface diffusion and chemisorption kinetics.

[0020] Furthermore, before introducing the mixed gas in step S3, an inert protective gas (preferably argon) is introduced into the chemical vapor deposition system to purge the reaction chamber for 30 to 60 minutes at a flow rate of 200 to 500 sccm. sccm stands for Standard Cubic Centimeter per Minute, which represents the volume of gas flowing through a cross section per minute (in cubic centimeters or milliliters) under standard temperature and pressure conditions (0°C, 1 atm).

[0021] Furthermore, in step S4, the mixed gas consists of argon and hydrogen, with a hydrogen flow rate of 1 to 10 sccm and an argon flow rate of 60 to 150 sccm. The appropriate argon flow rate can effectively control the precursor vapor concentration gradient, achieving uniform growth of tin-based sulfides SnS2, Sn2S3, and SnS. At the same time, the appropriate hydrogen flow rate can effectively reduce the activation energy required for the reaction, which is more conducive to the growth of tin-based sulfides SnS2, Sn2S3, and SnS.

[0022] Furthermore, in step S4, the heating time from room temperature to growth temperature is 20 to 30 minutes, preferably 25 to 30 minutes, and the holding time at the growth temperature is 8 to 15 minutes, preferably 10 to 12 minutes.

[0023] Furthermore, after the reaction in step S4 is completed, the chemical vapor deposition system is naturally cooled, which is carried out in a mixed atmosphere.

[0024] The tin-based sulfide material obtained by the above preparation method is a nanostructure. The nanostructure is directly grown on an FTO conductive glass substrate, and its phase is one of SnS2, Sn2S3 or SnS, wherein SnS2 has a plate-like morphology, and Sn2S3 and SnS have a granular morphology.

[0025] The tin-based sulfide materials obtained by the above preparation method can be used in the preparation of optoelectronic devices, catalytic devices or energy storage devices.

[0026] Compared with existing processes, the beneficial effects of this technical solution are as follows:

[0027] (1) This invention uses FTO conductive glass as a solid tin source and directly supplies the Sn source through in-situ reaction, overcoming the problems of low transport efficiency and uneven distribution of traditional powdered tin sources. This strategy optimizes the nucleation environment at the reaction interface, making the growth process of SnS2, Sn2S3, and SnS nanomaterials more efficient and controllable, while simplifying the process flow and reducing production costs.

[0028] (2) Based on atmospheric pressure chemical vapor deposition technology, the present invention uses solid sulfur powder as sulfur source, which avoids the use of highly toxic and corrosive precursors such as H2S and SnCl4 in traditional CVD process, significantly improves operation safety, reduces special requirements for equipment and environment, and provides the possibility for large-scale application.

[0029] (3) By precisely controlling key parameters such as the amount of sulfur powder and the growth temperature, this invention enables the directional synthesis of three different phase nanomaterials, SnS2, Sn2S3, and SnS, within the same technical system. The prepared materials exhibit good crystallinity, high purity, and uniform morphology, and demonstrate good stability in a normal atmospheric environment, laying a solid foundation for their intrinsic property research and device performance development. Attached Figure Description

[0030] Figure 1 This is a digital photograph of the SnS2 nanosheets in Example 1;

[0031] Figure 2 The optical microscopy characterization results of SnS2 nanosheets in Example 1 are shown below.

[0032] Figure 3 The results are Raman spectroscopic characterizations of the SnS2 nanosheets in Example 1.

[0033] Figure 4 The results are shown in the scanning electron microscope characterization of SnS2 nanosheets in Example 1.

[0034] Figure 5 The X-ray diffraction characterization results are for the SnS2 nanosheets in Example 1;

[0035] Figure 6 The X-ray photoelectron spectroscopy characterization results are shown for the SnS2 nanosheets in Example 1;

[0036] Figure 7 A digital photograph of the Sn2S3 nanomaterial in Example 2;

[0037] Figure 8 The optical microscopy characterization results of the Sn2S3 nanomaterials in Example 2 are shown below.

[0038] Figure 9 The results are Raman spectral characterizations of the Sn2S3 nanomaterials in Example 2.

[0039] Figure 10 The results of scanning electron microscopy characterization of Sn2S3 nanomaterials in Example 2 are shown.

[0040] Figure 11 The X-ray diffraction characterization results of the Sn2S3 nanomaterials in Example 2 are shown below.

[0041] Figure 12 The X-ray photoelectron spectroscopy characterization results of the Sn2S3 nanomaterials in Example 2 are shown below.

[0042] Figure 13 A digital photograph of the SnS nanomaterial in Example 3;

[0043] Figure 14 The optical microscopy characterization results of the SnS nanomaterials in Example 3 are shown below.

[0044] Figure 15 The results are Raman spectral characterizations of the SnS nanomaterials in Example 3.

[0045] Figure 16 The results of scanning electron microscopy characterization of SnS nanomaterials in Example 3 are shown.

[0046] Figure 17 The X-ray diffraction characterization results of the SnS nanomaterials in Example 3 are shown below.

[0047] Figure 18 The X-ray photoelectron spectroscopy characterization results of the SnS nanomaterials in Example 3 are shown below.

[0048] Figure 19 The optical microscopy characterization results of SnS2 nanomaterials (without hydrogen gas) in Comparative Example 1 are shown.

[0049] Figure 20 The optical microscopy characterization results of SnS nanomaterials in Comparative Example 2 (heating center temperature is 500℃);

[0050] Figure 21 The results show the Raman spectral characterization of SnS nanomaterials in Comparative Example 2 (heating center temperature is 500℃). Detailed Implementation

[0051] The technical solution of the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. However, it should be noted that the scope of protection of the present invention is not limited to the following embodiments.

[0052] Example 1

[0053] A 1 cm × 0.5 cm FTO glass substrate was used as the base. The FTO substrate was placed on a graphite sheet, and then the graphite sheet with the substrate was pushed into the center of the hot zone of a tube furnace. Following the upstream-to-downstream airflow direction, a quartz boat containing 250 mg of high-purity sulfur powder was placed upstream of the tube furnace, with the substrate at a distance of 22.5 cm from the heating center. First, argon gas was introduced at a flow rate of 500 sccm for 10 minutes to purge residual air from the chamber. Then, a hydrogen-argon mixture was introduced, with an argon flow rate of 85 sccm and a hydrogen flow rate of 5 sccm, continuously flowing into the reaction chamber to stabilize the gas environment inside the tube furnace. A heating program was then set: the heating center temperature was first raised from room temperature to 500℃ over 20 minutes, and then maintained at 500℃ for 10 minutes for the reaction. After the reaction system naturally cooled to room temperature, the hydrogen and argon gases were turned off, and the FTO substrate was removed, yielding SnS2 nanosheets. A digital photograph of these nanosheets is shown below. Figure 1 As shown.

[0054] The SnS2 nanosheets obtained in Example 1 were characterized by optical microscopy, Raman spectroscopy, scanning electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. The results are as follows: Figures 2 to 6 As shown. Optical and scanning electron microscopy revealed that SnS2 was deposited on the substrate surface and grew perpendicularly to the substrate to form hexagonal nanosheets. Raman spectroscopy characterization results indicated that the sample exhibited growth at 200 cm⁻¹. -1 With 310 cm -1 There are two distinct characteristic peaks, corresponding to the E values ​​of SnS2. g and A 1g Two vibrational modes were observed, consistent with previous reports. X-ray diffraction characterization showed that the diffraction peaks of SnS2 nanosheets at 14.9°, 28.0°, 31.9°, 41.7°, 49.8°, and 52.2° corresponded well to the (001), (100), (101), (102), (110), and (111) crystal planes of hexagonal SnS2 (PDF#23-0677). X-ray photoelectron spectroscopy characterization showed that in SnS2, Sn... 4+ Sn 3d 3 / 2 and 3D 5 / 2 The orbits are located at 494.3 eV and 485.9 eV, S 2- S 2p 3 / 2 and S 2p 1 / 2 The orbits are located at 161.1 eV and 162.3 eV, which is largely consistent with previous reports.

[0055] Example 2

[0056] By changing the mass of S powder in Example 1 to 75 mg, while keeping other preparation conditions unchanged, Sn2S3 nanomaterials can be obtained, as shown in the digital photograph. Figure 7 As shown.

[0057] The Sn₂S₃ nanomaterials obtained in Example 2 were characterized by optical microscopy, Raman spectroscopy, scanning electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. The results are as follows: Figures 8 to 12 As shown. Sn₂S₃ nanoparticles were observed deposited on the substrate surface using optical and scanning electron microscopy. Raman spectroscopy characterization results indicate that the sample... -1 69 cm -1 150 cm -1 232 cm -1 And 304 cm -1 The characteristic peak at that point corresponds to the A of Sn2S3. 1gVibration mode; 249cm -1 The characteristic peak at that point corresponds to the B of Sn2S3. 1g Vibrational modes. X-ray diffraction pattern characterization results show that the diffraction peaks of Sn2S3 at 26.6°, 31.9°, and 37.9° correspond well to the (111), (211), and (250) crystal planes of Sn2S3, respectively (PDF#14-0619), further proving the successful generation of Sn2S3 nanomaterials. X-ray photoelectron spectroscopy characterization results show that Sn in Sn2S3 has two oxidation states (Sn... 2+ and Sn 4+ ), Sn 4+ Sn 3d 3 / 2 and 3D 5 / 2 The orbitals are located at 493.7 eV and 485.3 eV, Sn 2+ Sn3d 3 / 2 and 3D 5 / 2 The orbits are located at 492.1 eV and 483.9 eV, S 2- S 2p 3 / 2 and S 2p 1 / 2 The orbits are located at 159.4 eV and 160.6 eV, which is consistent with previous reports.

[0058] Example 3

[0059] A 1 cm × 0.5 cm FTO glass substrate was used as the base. The FTO substrate was placed on a graphite sheet, and then the graphite sheet with the substrate was pushed into the center of the hot zone of a tube furnace. Following the upstream-to-downstream airflow direction, a quartz boat containing high-purity sulfur powder was placed at the upstream inlet of the tube furnace. The sulfur powder mass was 100 mg, and the distance between the substrate and the heating center was 22.5 cm. First, argon gas was introduced at a flow rate of 500 sccm for 10 minutes to purge the reaction chamber and remove residual air. Then, a hydrogen-argon mixture was introduced, with an argon flow rate of 85 sccm and a hydrogen flow rate of 5 sccm, continuously flowing into the reaction chamber to stabilize the gas environment inside the tube furnace. A heating program was then set: first, the temperature of the heating center was raised from room temperature to 600℃ over 30 minutes, and then maintained at 600℃ for 10 minutes for the reaction. After the reaction system naturally cooled to room temperature, the hydrogen and argon gases were turned off, the FTO substrate was removed, and SnS nanomaterials were obtained. A digital photograph of the obtained SnS nanomaterials is shown below. Figure 13 As shown.

[0060] The SnS nanomaterials obtained in Example 3 were characterized by optical microscopy, Raman spectroscopy, scanning electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. Figures 14 to 18As shown. Uniformly grown SnS nanoparticles on FTO were observed using optical and scanning electron microscopy, forming a thin film. Raman spectroscopy characterization results indicate that the sample exhibits [a certain characteristic] at 95 cm⁻¹. -1 158 cm -1 187 cm -1 220 cm -1 These four positions show distinct characteristic peaks, corresponding to the A peaks of SnS, respectively. 1 g B 2 3g A 2 g and A 3 g Four vibration modes, at 283 cm -1 The characteristic peak at that location also corresponds to the B peak of SnS. 2g The vibrational modes are consistent with previous reports, confirming the successful generation of SnS nanomaterials. X-ray diffraction pattern characterization results show that the diffraction peaks of SnS at 31.8° and 66.5° correspond well to the (040) and (171) crystal planes of orthorhombic SnS, respectively (PDF#39-0354). X-ray photoelectron spectroscopy characterization results indicate that in SnS, Sn... 2+ Sn 3d 3 / 2 and 3D 5 / 2 The orbits are located at 493.8 eV and 485.3 eV, S 2- S 2p 3 / 2 and S 2p 1 / 2 The orbitals are located at 160.8 eV and 161.9 eV. In addition, Sn was also found in SnS. 4+ Sn 3d 3 / 2 and 3D 5 / 2 The orbitals, located at 494.9 eV and 486.7 eV respectively, can be attributed to SnO2 formed by oxidation of the SnS surface.

[0061] Comparative Example 1

[0062] The process conditions were kept exactly the same as in Example 1, except that hydrogen gas was not introduced.

[0063] Experimental results show that the SnS2 nanosheets generated on the substrate after the reaction are sparsely distributed, such as... Figure 19 As shown, the size of the nanosheets is much smaller than that of the SnS2 nanosheets in Example 1. This indicates that hydrogen lowers the activation energy of the reaction, promoting further reaction of sulfur vapor with SnO2 to form SnS2 nanosheets. Therefore, the introduction of hydrogen is crucial for the growth of SnS2 nanosheets.

[0064] Comparative Example 2

[0065] The process conditions were kept exactly the same as in Example 3, except that the growth temperature was increased from 600°C to 650°C.

[0066] Experimental results show that although SnS was generated on the substrate after the reaction, the SnS was not uniformly distributed across the entire substrate, and the grown SnS was a molten mass, such as... Figure 20 As shown. Figure 21 The Raman spectral characterization results shown indicate that the sample at 94 cm⁻¹ -1 154 cm -1 183 cm -1 222 cm -1 These four positions show distinct characteristic peaks, corresponding to the A peaks of SnS, respectively. 1 g B 2 3g A 2 g and A 3 g Four vibrational modes confirmed that the grown sample was SnS nanomaterial. This indicates that excessively high temperatures can disrupt the uniformity of the nanostructure. Therefore, a suitable growth temperature is crucial for obtaining high-quality nanomaterials.

Claims

1. A method for preparing a nanostructured tin-based sulfide material, wherein the tin-based sulfide includes one of SnS2, Sn2S3, and SnS, the preparation method being based on a chemical vapor deposition system, using FTO conductive glass as the tin source and growth substrate, and solid sulfur powder as the sulfur source, comprising the following steps: S1. Place the FTO conductive glass in the constant temperature heating zone of the chemical vapor deposition system; S2. Place the source boat containing sulfur powder upstream of the constant temperature heating zone; S3. Introduce a mixture of protective gas and reducing gas into the chemical vapor deposition system; S4. The constant temperature heating zone is heated to 500℃~600℃ and kept at that temperature to allow the tin element released from the FTO conductive glass to react with gaseous sulfur, thereby growing a nanostructured tin-based sulfide material in situ on the substrate. in, By adjusting the amount of sulfur powder and the growth temperature of the constant-temperature heating center region, selective control of the tin-based sulfide phase can be achieved, thereby obtaining one of the target tin-based sulfides SnS2, Sn2S3, and SnS.

2. The method for preparing the nanostructured tin-based sulfide material according to claim 1, characterized in that, The specific methods for achieving selective control are as follows: When the amount of sulfur powder used is 100~250 mg and the growth temperature is 500~550℃, the target tin-based sulfide is SnS2. When the amount of sulfur powder used is 25~75 mg and the growth temperature is 500~550℃, the target tin-based sulfide is Sn2S3. When the amount of sulfur powder used is 80~120 mg and the growth temperature is 580~600℃, the target tin-based sulfide is SnS.

3. The method for preparing the nanostructured tin-based sulfide material according to claim 1, characterized in that, In step S1, the sheet resistance of the FTO conductive glass is 7 to 14 ohms and the thickness is 1.8 to 3.5 mm.

4. The method for preparing the nanostructured tin-based sulfide material according to claim 1, characterized in that, In step S2, the purity of the sulfur powder is not less than 99.9%, and the distance between the source boat and the center of the constant temperature heating zone is 21.5 cm to 24.5 cm.

5. The method for preparing the nanostructured tin-based sulfide material according to claim 1, characterized in that, Before introducing the mixed gas in step S3, an inert protective gas is introduced into the chemical vapor deposition system to purge the reaction chamber for 30 to 60 minutes at a flow rate of 200 to 500 sccm.

6. The method for preparing the nanostructured tin-based sulfide material according to claim 1, characterized in that, In step S4, the mixed gas consists of argon and hydrogen, with a hydrogen flow rate of 1 to 10 sccm and an argon flow rate of 60 to 150 sccm.

7. The method for preparing the nanostructured tin-based sulfide material according to claim 1, characterized in that, In step S4, the heating time from room temperature to growth temperature is 20-30 minutes, and the holding time at the growth temperature is 8-15 minutes.

8. The method for preparing the nanostructured tin-based sulfide material according to claim 1, characterized in that, After the reaction in step S4 is completed, the chemical vapor deposition system is naturally cooled, which is carried out in a mixed atmosphere.

9. The tin-based sulfide material obtained by the preparation method according to any one of claims 1 to 8, characterized in that, The tin-based sulfide material is a nanostructure, which is directly grown on an FTO conductive glass substrate. Its phase is one of SnS2, Sn2S3 or SnS, wherein SnS2 has a plate-like morphology and Sn2S3 and SnS have a granular morphology.

10. The application of the tin-based sulfide material as described in claim 9 in the preparation of optoelectronic devices, catalytic devices or energy storage devices.

Citation Information

Patent Citations

  • Method for phased synthesis of SnS, SnS2 or SnS / SnS2 heterojunction nanocrystalline material by one-step process

    CN102897827A

  • Method for preparing stannous sulfide nanosheet array film

    CN103819098A

  • Method for preparing stannic sulfide / antimony trisulfide / stannous sulfide heterojunction film

    CN105977334A

  • Rhenium disulfide nanosheet used for hydrogen evolution reaction, and preparation method and applications thereof

    CN110467358A

  • Preparation method of ZnO / ZnS composite film and ultraviolet photoelectric detector thereof

    CN111268921A